Development of an Integrated Science and Health Education Module Based on Discovery Learning Theme Sports Healthy Heart - Mukholid, Agus (Jurnal Penelitian Pendidikan IPA, 2024)
This research aims to analyze the validity, practicality and readability of the Integrated Science module based on discovery learning on the theme of healthy heart sports. This research is research and development. The development model used is the 4D model by Thiagarajan which contains three development stages, namely define, design and develop. The validity assessment included two science education experts and the practicality assessment included five science teachers at SMP Negeri 2 Bekasi. The test subjects for the Integrated Science module included ten students in class VIIIA of SMP Negeri 2 Bekasi Sukasada in the readability test. The data obtained consisted of qualitative data and quantitative data using observation guide grid instruments, interview guide grids and questionnaire assessment sheets. Data were analyzed descriptively. Research results The Integrated Science Module obtained a score of 1 with very valid qualifications based on the results of the Science Education Expert's assessment with a score of 1; The Integrated Science Module obtained a score of 4.35 with very practical qualifications based on the science teacher's assessment; The Integrated Science Module obtained a score of 4.14 with a reading qualification based on the results of student assessments with a score of 4.14. The conclusion of this research is that the Integrated Science module based on discovery learning with the theme of healthy heart sports has very valid qualifications, is very practical and readable, so it can be continued to effectiveness testing